The Effectiveness of Using Mind Mapping Techniques to Improve Students' Speaking Skills - Renda Lestari; Ridho Kurniawan; Anjeli Puteri (LPPM Universitas Muhammadiyah Muara Bungo, 2026)
This study concentrated on assessing the effects of the mind mapping technique on enhancing students' speaking skills, tackling the frequent difficulty of articulating thoughts in English. The research was driven by students' difficulties in communication stemming from a lack of motivation, fear of making errors, and limited vocabulary. Conducted as a pre-experimental quantitative study at SMP Negeri 4 Muara Bungo, the research involved 30 eighth-grade students from class VIII 6, selected through cluster random sampling. Data gathering involved a preliminary test, an intervention phase, and a final assessment.. The results revealed a significant improvement in speaking performance, with mean scores increasing from 55. 00 in the initial assessment to 67. 83 in the final assessment.The t-test value of 7.409 exceeded the critical t-value of 2.034 at the significance level, confirming the intervention's effectiveness. Furthermore, the normality test values improved from 2.87 to 7.22, reflecting a total gain of 4.35 in speaking ability. In conclusion, The method of mind mapping was found to be extremely useful in improving the oral communication abilities of eighth graders at SMPN 4 Muara Bungo by providing a structured visual framework that enables students to organize and articulate their ideas with greater confidence.